2016
DOI: 10.1007/s00167-016-4265-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical comparison of the two-stranded single and four-stranded double Krackow techniques for acute Achilles tendon ruptures

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…The mean age of the patient was 36.14 years (18-67), mean duration of symptom presented was 6.08 days (1 to 18). The average hospital stay after surgery was 5.56 days (4 to 11), and mean follow up at point A was 14.14 months (12)(13)(14)(15)(16)(17)(18) and at point B was 30.76 months (24-39).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mean age of the patient was 36.14 years (18-67), mean duration of symptom presented was 6.08 days (1 to 18). The average hospital stay after surgery was 5.56 days (4 to 11), and mean follow up at point A was 14.14 months (12)(13)(14)(15)(16)(17)(18) and at point B was 30.76 months (24-39).…”
Section: Resultsmentioning
confidence: 99%
“…Operative procedure was performed by end-to end repair of ruptured AT using two-stranded single Krackow suturing technique. 15 Postoperatively, patients were put on below knee plaster cast for six weeks. Followup for functional outcome was done at one and two years.…”
Section: Methodsmentioning
confidence: 99%
“…Although there was only two strand Krachow suture in the proximal stump of JKIB, the looped percutaneous suture of distal stump increased the numbers of strand crossing the repair site in JKIB to six. Biomechanically, the number of strand between each group should be constant to made the result valid, but the four strand end to end Krachow suture is still the benchmark in Achilles open repair clinically [6,9,29,36,37]. Thus, it was still reasonable that the 4Sk was chosen as comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Although the clinical outcome of the case series was well, the suture strength has not yet been validated. Accordingly, we chose the four-strand Krackow suture (4sK) for comparison since this suture is favored for open repair due to easily performed and well clinical outcome and in previous publication [29]. In addition, we chose the triple-bundle technique (TBS) as another suture for comparison because it was shown to be stronger than the 4sK suture in a biomechanical study [30].…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al found equally favorable clinical outcomes, isokinetic muscle strength, and a low complication rate with the two-stranded single Krackow technique as compared with the fourstranded double Krackow technique for acute Achilles tendon rupture repair. 5 Using simulated early rehabilitation biomechanical testing, Van Dyke et al showed that Giftbox-modified Krackow Achilles repair technique with FiberWire suture was stronger and more resistant to gap formation at the repair site than combinations that incorporated the Bunnell stitch or Ultrabraid suture. 2 Hong et al found no difference in cyclic load and load to failure between needleless knot techniques and Krackow configurations.…”
Section: See Related Article On Page 663mentioning
confidence: 99%